Perkembangan Kualitas Lubang Komposit Serat Daun Nanas dengan Menggurdi Bertahap Kecepatan Tinggi - Mahdi, Whiko Androser; Mulyadi, Ismet Hari (Jurnal Teknik Mesin, 2024)
Composites are materials consisting of reinforcement and matrix. Reinforcing materials of composites consist of synthetic materials and natural fiber materials. One of the natural fibers that is currently being developed is pineapple leaf fiber, where several studies have found several ways to process pineapple leaf fiber so that it can be used as a substitute for synthetic fibers. One of the studies is looking for good machining parameters to process pineapple leaf fiber with a peck drilling canned cycle process which in this research objectives to see how the development of hole quality in the peck drilling canned cycle process. The stage in this research starts from the material being drilled with the stepwise dredging method, after the dredging process the holes are viewed using a digital microscope and then measured using Digimizer image processing software. The results of this study are roundness deviation, cylindricity deviation, axis perpendicularity deviation, and delamination ratio. The results obtained from this study will be subjected to statistical tests in order to obtain tested values using the ANOVA statistical test with the approach used, namely the fisher individual test in order to see the real impact of the machining process carried out.